1999
DOI: 10.1212/wnl.52.4.743
|View full text |Cite
|
Sign up to set email alerts
|

Postictal nose-rubbing in the diagnosis, lateralization, and localization of seizures

Abstract: Nose-rubbing is an easily observed phenomenon, has high interobserver reliability, and provides useful lateralizing information in patients with TLE. It was less frequently seen in extratemporal lobe epilepsy and was not seen after generalized seizures or nonepileptic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 8 publications
5
24
0
1
Order By: Relevance
“…The other was hemiplegic and had contralateral FW. All the other patients had, sometimes, ipsilateral or, sometimes, contralateral postictal FW, so without lateralizing value, in accordance with literature data [6,53].…”
Section: Neuroethology As a Reliable Quantitative Tool To Characterizsupporting
confidence: 90%
See 1 more Smart Citation
“…The other was hemiplegic and had contralateral FW. All the other patients had, sometimes, ipsilateral or, sometimes, contralateral postictal FW, so without lateralizing value, in accordance with literature data [6,53].…”
Section: Neuroethology As a Reliable Quantitative Tool To Characterizsupporting
confidence: 90%
“…The involvement of the contralateral limb in dystonia, in tonic postures, or due to the occurrence of paresis or neglect could explain the ipsilateral predominance of the facial wiping in TLE [18,51]. In extratemporal epilepsy, however, it is less frequent and without lateralizing value in FLE seizures [6,53]. The postictal facial wiping behaviors in our group were observed in 11 patients and were exclusively unilateral only in two patients.…”
Section: Neuroethology As a Reliable Quantitative Tool To Characterizmentioning
confidence: 56%
“…They are less common in patients with extratemporal onset seizures and we reported that they also accompany absence seizures (32,33). Activation of the central autonomic network, particularly the amygdala, is thought to lead to nasal secretion.…”
Section: Peri-ictal Respiratory Changesmentioning
confidence: 78%
“…During a complex partial seizure, the contralateral arm may assume a tonic posture (53). After a seizure semivoluntary events as mundane as nose wiping tend to be done with the hand ipsilateral to the seizure focus (19,24). EEG may reveal focal postictal delta (slow) activity marking the seizure focus in more than half of studied cases (27).…”
Section: Localizing Value Of the Postictal Statementioning
confidence: 99%